2021
DOI: 10.3390/en14040963
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Ultrasonic Field on the Efficiency of Coke Wastewater Treatment in a Sequencing Batch Reactor

Abstract: The growing production of coke and, consequently, coke wastewater is a significant problem for the environment. Coke wastewater, because it contains high amounts of toxic substances, is classified as an extremely hazardous industrial wastewater. The treatment of such wastewater requires a combination of advanced physicochemical and biological methods. The aim of the research was to investigate the effectiveness of the application of the ultrasonic disintegration of coke wastewater in a sequencing batch reactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Biological treatment methods, such as the anoxic-oxic (A-O), anaerobic-anoxic-aerobic (A1-A2-O), and sequencing batch reactor (SBR) systems, are commonly employed for treating coking wastewater [5][6][7]. Studies have indicated that the organic constituents in coking wastewater can adversely affect these biological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Biological treatment methods, such as the anoxic-oxic (A-O), anaerobic-anoxic-aerobic (A1-A2-O), and sequencing batch reactor (SBR) systems, are commonly employed for treating coking wastewater [5][6][7]. Studies have indicated that the organic constituents in coking wastewater can adversely affect these biological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of these processes is dephenolation of wastewater; however, other hazardous organic and inorganic wastes are also removed during this process, such as oils and tars, slurries, free and fixed ammonia, volatile and nonvolatile phenols, thiosulfates, hydrogen sulfide, and highly toxic substances such as cyanides and rhodonites [ 9 , 10 ]. It should be noted that the application of conventional treatment methods, based on activated sludge technology, is not always efficient [ 1 , 11 ]. Because of that, the development of new methods is required.…”
Section: Introductionmentioning
confidence: 99%